2018
DOI: 10.1155/2018/5943759
|View full text |Cite
|
Sign up to set email alerts
|

The Neural and Behavioral Correlates of Anomia Recovery following Personalized Observation, Execution, and Mental Imagery Therapy: A Proof of Concept

Abstract: The impact of sensorimotor strategies on aphasia recovery has rarely been explored. This paper reports on the efficacy of personalized observation, execution, and mental imagery (POEM) therapy, a new approach designed to integrate sensorimotor and language-based strategies to treat verb anomia, a frequent aphasia sign. Two participants with verb anomia were followed up in a pre-/posttherapy fMRI study. POEM was administered in a massed stimulation schedule, with personalized stimuli, resulting in significant i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…They demonstrated a significant change in functional connectivity in the right sensorimotor networks when a significant linguistic improvement was present, suggesting that this therapy improves naming abilities in aphasic patients. Even more recently, Durand et al (2018), explicitly attributed their rehabilitation approach (Personalized Observation, Execution, and Mental imagery therapy, POEM) to the recent evidence of the embodied framework and identified the neural substrate of their approach via neuroimaging before and after intervention. They combined the potential of action observation, gesture execution and mental imagery into the therapy of two aphasic patients (i.e., proof of concept study).…”
Section: Studies On L2 Embodiment Serving Clinical Purposesmentioning
confidence: 99%
“…They demonstrated a significant change in functional connectivity in the right sensorimotor networks when a significant linguistic improvement was present, suggesting that this therapy improves naming abilities in aphasic patients. Even more recently, Durand et al (2018), explicitly attributed their rehabilitation approach (Personalized Observation, Execution, and Mental imagery therapy, POEM) to the recent evidence of the embodied framework and identified the neural substrate of their approach via neuroimaging before and after intervention. They combined the potential of action observation, gesture execution and mental imagery into the therapy of two aphasic patients (i.e., proof of concept study).…”
Section: Studies On L2 Embodiment Serving Clinical Purposesmentioning
confidence: 99%
“…These findings provide preliminary results on how factors impacting the contextual presence of an embodiment effect can be exploited in what they call 'action observation therapy', and encourage the testing of new action-based treatments to recover language disease(Picano, Quadrini, Pisano, & Marangolo, 2021). Besides action observation therapies, other treatments have already been proposed, based on the interaction between the motor and language systems, including Semantic Feature Analysis therapy(Boyle & Coelho, 1995), personalized observation, execution, and mental imagery therapy(Durand & Ansaldo, 2013;Durand, Berroir, & Ansaldo, 2018;Durand, Masson-Trottier, Sontheimer, & Ansaldo, 2021), gesture production therapies(Goldin-Meadow, Nusbaum, Kelly, & Wagner, 2001;Rose, Attard, Mok, Lanyon, & Foster, 2013) and language-action therapies(Difrancesco, Pulvermüller, & Mohr, 2012;Stahl et al, 2018). In a similar vein, neuromodulation studies have shown that stimulating the motor cortex(Branscheidt, Hoppe, Zwitserlood, & Liuzzi, 2017;Meinzer, Darkow, Lindenberg, & Flöel, 2016) and even cerebellar and spinal cord (seePisano & Marangolo, 2020) facilitate verb retrieval in PWA.…”
mentioning
confidence: 95%
“…For the ten participants in this study, it could contribute to explain why, even if they presented variable anomia breakdown loci, they all benefited from FR-PCA. Moreover, as per previous work in our lab [ 34 , 44 , 45 , 46 , 47 ] and following the original protocol [ 20 ], frequency and dosage (3 times per week for 5 weeks total, approximately 60 min sessions) ensure the feasibility of Fr-PCA in the clinical practice in Quebec. Moreover, these therapy variables correspond to optimal variable ranges in terms of minutes per session [ 65 , 66 ], the number of sessions weekly [ 65 , 66 ], and cumulative dosage [ 66 ] reported in previous studies on naming therapies that improve naming performance in persons with aphasia.…”
Section: Discussionmentioning
confidence: 97%
“…The experimental protocol is similar to previous studies conducted in our lab [ 34 , 44 , 45 , 46 , 47 ]. A baseline evaluation was completed prior to therapy, including a language assessment and an initial fMRI session (T0).…”
Section: Methodsmentioning
confidence: 95%